PF-13 Fracture Fixation between Os Lumbalis II and III on a Three Month Old Kitten Using Parallel Technique - Siti Zaenab; Ivan Satriawan; Osye S Alamsari; Eva Zulfiati; Benda Alifianti; . Hidayati; Deni Noviana (Hemera Zoa, 2018)
Spinal fractures, luxations, and fracture- luxations in dogs and cats are common and are often the result of vehicular injury. Other frequent causes of injury include animal attacks or falling from a height. Reports that describe the distribution of spinal column injuries indicate that they affect the lumbar vertebrae most frequently, followed by sacrococcygeal, thoracic, and cervical vertebrae2,3.